Responsible management of shifts in work modes. volume 1 : values for a post pandemic future - Ogunyemi, Kemi; Onaga, Adaora I. (Emerald Publishing Limited, 2022)
The Covid-19 pandemic is leaving an indelible mark on history leaving a heightened need for responsibility, accountability, and ethics in the use and management of resources for the common good. This first volume of Responsible Management of Shifts in Work Modes - Values for a Post Pandemic Future reflects on past and present events influencing the pandemic's global impact and the shifts towards new directions in responsible management of human relationships and workforce dynamics. Our post-pandemic world requires active agency to ensure that it places work in its right context for growth and development; this entails greater responsibility for those whose decisions impact others' physical, psychological, and spiritual health. Considering the organisations that have borne the direct impact of the changes and the challenges to the health sector, Responsible Management of Shifts in Work Modes - Values for a Post Pandemic Future, Volume 1 unpacks what responsible management means, explores future adaptions to heighten responsibility and proffers recommendations. Case studies within present examples to guide others who wish to act responsibly with an intentional focus on the future of work and management which are rapidly evolving and require deep reflections about their direction and its quality. In the wake of the pandemic, Responsible Management of Shifts in Work Modes - Values for a Post Pandemic Future will aid businesses by providing insights on how to responsibly react to changes caused by the pandemic; by reinforcing their ongoing efforts and by broadening their perspectives.